2014
DOI: 10.1080/10826076.2014.968666
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Enantiomers of Selected Sulfur-Containing Amino Acids by Using Serially Coupled Achiral-Chiral Columns

Abstract: Homocysteine is an important indicator of human health. Increased levels of plasma homocysteine are associated with a higher risk of cardiovascular, cerebrovascular and peripheral arterial disease. Homocysteine is naturally occurring amino acids and it is formed during the methionine metabolism. It can be either transsulfurated to cysteine or remethylated to methionine. Therefore, the simultaneous monitoring of homocysteine, cysteine and methionine is often desirable. Many studies are focused on the achiral se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Experimentally, separation of amino acids into each pure enantiomer usually requires very long chromatographic columns due to the very small differences in the interactions of each enantiomer with the chiral stationary phase. 32 Likewise, the difference in the interaction for the L-L and the L-D pairs is also expected to be small throughout the PMF profile. Specifically at the global minima (ξ = 5.5 Å) the difference amounted to only ∆∆A = 0.05 kJ/mol and at their second minima (ξ = 6.9 Å) to only ∆∆A = 0.08 kJ/mol, both much lower than k B T at T = 300 K.…”
Section: Chiral Discriminationmentioning
confidence: 99%
“…Experimentally, separation of amino acids into each pure enantiomer usually requires very long chromatographic columns due to the very small differences in the interactions of each enantiomer with the chiral stationary phase. 32 Likewise, the difference in the interaction for the L-L and the L-D pairs is also expected to be small throughout the PMF profile. Specifically at the global minima (ξ = 5.5 Å) the difference amounted to only ∆∆A = 0.05 kJ/mol and at their second minima (ξ = 6.9 Å) to only ∆∆A = 0.08 kJ/mol, both much lower than k B T at T = 300 K.…”
Section: Chiral Discriminationmentioning
confidence: 99%
“…Separation was found to be influenced by both the eluent pH and the MeOH content of 0.1% TEAA (pH 4.1)/MeOH mobile phase, where a different retention mechanism was suggested to interpret the retention behavior observed at high MeOH contents. Lehotay et al [ 40 , 41 ] investigated the enantioseparation of Cys, homo-Cys, and Met as standards, and in human plasma with 2D-HPLC technique applying a Purospher C18 in the first and Chirobiotic TM T or TAG in the second dimension. Separations were optimized using RP conditions, where amino acids were separated in the first, while their enantiomers in the second dimension.…”
Section: Recent Applications Of Different Macrocyclic Antibiotic-based Cspsmentioning
confidence: 99%
“…Lehotay's research group reported a two-dimensional HPLC-ECD method for determination of the enantiomers of Hcy, Cys, and Met using a combination of ODS and teicoplanin aglycone columns [69,70]. The chiral separation of Hcy, Cys, and Met enantiomers was realized in a single 130 min analytical run.…”
Section: Electrochemical Detectionmentioning
confidence: 99%